Centro La Familia Fundraiser with Justice Cruz Reynoso at Elks Lodge - Watkins, Howard::::::::: (1983)
Justice George Brown, Justice Cruz Reynoso, Patience Milrod, Diego Mendizabel Bowing heads as ? Gives benediction